On the principles of Japanese forest policy since 1950. - Handa, Ryoichi (Silva Fennica, 1986)
In Japan many governmental projects have been promoted during 35 years since 1950, which were most active in the history of our forestry and wood industry. They were pushed forward for and by high economic growth. This article refers to the development of our forest policy and projects in those days. But as for the future of the forest economics, it is an urgent question to develop the comparative study between every nationâs experience. In order to contribute to this problem, the forest policy is divided into three fields and experiences are discussed.